Positioning Health Equity Within a Systems Thinking Framework to Evaluate Coalitions and Collaborative Initiatives. Issue 165 (18th March 2020) - Hilgendorf, Amy E.; Moore, Travis R.; Wells, Alexandra; Stanley, Julia
Abstract: Evaluating coalitions and other community‐driven efforts demands new approaches that can account for the complexity of collaborative efforts and inform ongoing innovation, including efforts to advance health equity. In this chapter, we present an evaluation framework developed in partnership between a university and local health coalition that combines systems thinking and equity principles. We first describe the evaluation needs and priorities of coalitions like this one that seeks to work across sectors to advance health equity, and then describe the framework and the ways it can bridge systems thinking and equity in evaluation. We illustrate the framework through our work with a specific coalition and conclude the chapter with lessons learned and future directions for evaluators.